Land-cover Dynamics and Oriental Honey-buzzard Winter Habitat Preference in Borneo, Indonesia - Utami Meirani; Lilik Budi Prasetyo; Yeni A. Mulyani; Syartinilia; Horoyoshi Higuchi (Journal of Natural Resources and Environmental Management)
Migration is part of an individual's behavioral adaptation to seasonal environmental changes. Migration can take advantage of organisms facing cyclical changes in limited resources. Borneo island is one of the wintering migration destinations for Oriental Honey-buzzard in Indonesia. The confluence of deforestation, industrialization, and urbanization has placed Kalimantan at a critical juncture. Borneo Island has led to the fragmentation habitat. ARGOS is a satellite tracking tool that has been used to monitor the movements and behavior of Oriental Honey-buzzards since 2003. Three individuals were investigated in this study to determine the response to land-cover changes that occurred in Borneo in 2003, 2006, and 2009. The ecological complexity and speciesenvironment connections that support Oriental Honey-buzzard responses are highlighted in this study. The analysis of responses suggests that Oriental Honey-buzzard was more commonly encountered in forested areas in Borneo than in 11 other land-cover areas during three years 2003, 2006, and 2009. Time duration spent in forested areas consistently exhibited the longest presence duration, with durations of 136.88 hours, 1,121.17 hours, and 1,160.53 hours in 2003, 2006, and 2009, respectively. The shortest duration of presence in mangrove and swamp areas was during 2003, 2006, and 2009.